4-aperture differential image motion monitor as a new approach for estimating atmospheric turbulence parameters. Issue 7 (16th April 2019) - Dibaee, B.; Shomali, R.; Khalilzadeh, J.; Jafari, A.; Amniat-Talab, M.
ABSTRACT: The present study aims to evaluate the possibility of simultaneous measurements of Fried parameter and atmospheric Zernike defocus by measuring defocus aberration with 4-aperture differential image motion monitor (DIMM) for a portable telescope. Based on the results, a relation was observed between the variances of the defocus aberration (4-aperture defocus) and Fried parameter for G-tilt and Z-tilt methods. In addition, the variance of the 4-aperture defocus was compared with those of the Zernike defocus and the conventional DIMM and the results indicated a linear relationship. Based on the telescope and 4-aperture specifications, the variance of the 4-aperture defocus was converted into the Zernike defocus or the DIMM variances. Finally, the ability of estimating atmospheric coherence time by measuring the variance of the Zernike defocus velocity or the sum of the variances of two astigmatisms velocities with 4-aperture DIMM was investigated.